The Existence of Islamic Book Publishers in Medan City (1950-1990) - Saidatul Khairiyah; Haidar Putra Daulay; Hasan Asari (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
Book publishers are a symbol of progress and civilization. The city of Medan was once the "prima donna" of book publishing in the 1990s. In the 2000s era, Medan was no longer the center of book publishing like the previous era. This article aims to analyze the existence of Islamic book publishers in Medan City in 1950-1990. This research uses a qualitative approach with a literature study method. Data acquisition, analysis, to test the validity of the data using reference materials. The results of this study indicate that the existence of Islamic book publishers in Medan City is not in doubt. Although currently the number of Islamic book publishers is very small, Islamic book publishers in Medan City have experienced a moment of progress. The existence of Islamic book publishers certainly greatly influences the transmission of knowledge, especially religious sciences. The death of the book industry, especially Islamic books, cannot be avoided. Various situations and conditions of the community also greatly affect the sustainability of the business of publishing Islamic books in the city of Medan. Considering the big role of publishers in disseminating knowledge, there should be efforts from related parties such as the government to revive publishing businesses, especially publishers of Islamic books. Because the existence of publishers is very important in building the intellectual quality of the nation. Considering the big role of publishers in disseminating knowledge, there should be efforts from related parties such as the government to revive publishing businesses, especially publishers of Islamic books. Because the existence of publishers is very important in building the intellectual quality of the nation. Considering the big role of publishers in disseminating knowledge, there should be efforts from related parties such as the government to revive publishing businesses, especially publishers of Islamic books. Because the existence of publishers is very important in building the intellectual quality of the nation.